Pelatihan Manajemen Organisasi dan Kepemimpinan di Kelurahan Batulayar, Desa Batulayar, Lombok Barat - Abdurrahman Abdurrahman; Isra’ Dewi Kuntary Ibrahim; Rini Anggriani; Mochamad Najib Rodhi; Irwan Cahyadi; Raden Bagus Faisal Bagus Faisal Irany Sidharta; M. Thonthowi Jauhari; Puspita Dewi; Rangga Mulya Jati; Gustu Yudi Artha; Mimi Fadila (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
This training aims to provide organizational and leadership knowledge in running and managing an organization through the application of appropriate organizational management and leadership based on the characteristics of an organization. Organizational management is useful to determine the success and sustainable development in the midst of the times in the current era of globalization, an organization must have a good system. A good organization should have members who have adequate management knowledge in running an organization so that the vision and mission can be achieved according to the goals and or ideals of the organization and stakeholders. The results of this training activity showed that the level of understanding of the participants had increased, as evidenced by the results of the discussion of the case as well as problem solving and finding solutions presented by the participants in accordance with the material presented previously. The importance of this training for the organization is because the existence of this training will provide added value for the management and members of the organization so that they can run their organizations effectively and efficiently so as to achieve the stated organizational goals.